2015
DOI: 10.1155/2015/965804
|View full text |Cite
|
Sign up to set email alerts
|

Insights in Behavior of Variably Formulated Alginate-Based Microcapsules for Cell Transplantation

Abstract: Alginate-based microencapsulation of live cells may offer the opportunity to treat chronic and degenerative disorders. So far, a thorough assessment of physical-chemical behavior of alginate-based microbeads remains cloudy. A disputed issue is which divalent cation to choose for a high performing alginate gelling process. Having selected, in our system, high mannuronic (M) enriched alginates, we studied different gelling cations and their combinations to determine their eventual influence on physical-chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The swelling behaviour can occur mainly due to the osmotic factors. In PBS, high concentration of Na + can cause bead swelling, but in some studies, alginate beads showed the elasticity without showing membrane breakage [31]. In this experiment, high purity of alginate was employed to avoid over-swelling.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The swelling behaviour can occur mainly due to the osmotic factors. In PBS, high concentration of Na + can cause bead swelling, but in some studies, alginate beads showed the elasticity without showing membrane breakage [31]. In this experiment, high purity of alginate was employed to avoid over-swelling.…”
Section: Discussionmentioning
confidence: 97%
“…Assessment of bead swelling was aimed to determine the stability of the beads. In some conditions, alginate beads can swell resulted in the increasing of porosity and bead damage [31]. The swelling behaviour can occur mainly due to the osmotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, most of divalent cations (Ca 2+ , Sr 2+ , Cd 2+ , Co 2+ , Cu 2+ , Mn 2+ , Ni 2+ , Pb 2+ and Zn 2+ ) and some trivalent cations (Fe 3+ , Cr 3+ , Al 3+ , Ga 3+ , Sc 3+ and La 3+ ) can interact with G-blocks regions of alginate in a highly cooperative manner, generating a 3D network according to the so-called "egg-box" model [122]. Alginate affinity towards such polyvalent cations is directly dependent on the amount of G-blocks present in the alginate structure [123,124]. As demonstrated in [125] by numerous competitive inhibition studies, the main involved gelation mechanism is the dimerization of G residues.…”
Section: Alginate Ionic Cross-linkingmentioning
confidence: 99%
“…However, this reaction is still poorly understood. In fact, in addition to the use of polycations in the microcapsules formulation, many other factors can be involved in the immune response such as the alginate purity, the biocompatibility of the materials conforming the microcapsule, the alginate chemical composition (guluronic/mannuronic ratio) and the size of the microcapsules [24,73,74].…”
Section: Microencapsulationmentioning
confidence: 99%